KAJI SIFAT MEKANIK SAMBUNGAN LAS BUTT WELD DAN DOUBLE LAP JOINT PADA MATERIAL BAJA KARBON RENDAH - Azwinur Azwinur; Syukran Syukran; Hamdani Hamdani (University of Muhammadiyah Jakarta, 2018)
Technology in the field of steel construction continues to grow rapidly, especially in design and product design. In the application of steel construction is often a process of metal grafting or often called welding. Each welding process must have a joint design that serves to obtain a good connection or pass the test according to standard or code adopted. Therefore, the selection of welded joint type is very important before welding process. The purpose of this research is to know the value of tensile strength and bend strength (mechanical properties) welding joint type butt weld and double lap joint on material ASTM SA.36. Based on the test data it is found that the highest tensile strength test is in the welded butt weld type of 49.8 kgf/mm2 compared to the tensile strength value for the weld joint double joint type of 48.65 kgf/mm2. While the value of bending strength is greater in the joint weld type double lap joint than the welded butt weld type joint both for the category of root bend and face bend.